Leptospira seroprevalence in owned dogs from Spain. Issue 8 (August 2019) - López, M.C.; Vila, A.; Rodón, J.; Roura, X.
Abstract: Leptospira is a widespread zoonosis that has been linked to transmission between dogs and humans. The main purposes were to determine the seroprevalence of anti- Leptospira serum antibody and to identify the most common serovars in dogs in Spain. This is a cross-sectional study with 1, 310 records of canine Leptospira testing data from Spain since 2015 to 2017. Inclusion criteria were individual cases with MAT test results for 8 serovars (Bratislava, Icterohaemorrhagiae, Australis, Pomona, Grippotyphosa, Autumnalis, Canicola and Saxkoebing) and to have the zip code data. Three hundred and thirty-eight samples (25.8%; 95%CI 23.6–28.4) were seropositive (≥1:100). According to geographic areas, North had the highest seroprevalence (38.0%; 95%CI 28.9–47.1) followed by South (29.4%; 95%CI 20.1–38.8), Center (28.6%; 95%CI 24.3–33.0), Mediterranean (22.3%; 95%CI 19.1–25.6) and Northwest (22.2%; 95%CI 7.9–36.4). Seropositivity (MAT ≥1:100) was most common to serovars Icterohaemorrhagiae (19.4%; 95%CI 17.2–21.5) and Bratislava (8.5%; 95%CI 7.0–10.0), followed by Grippotyphosa (7.2%; 95%CI 5.8–8.6), Australis (6.4%; 95%CI 5.0–7.7), Autumnalis (5.0%; 95%CI 3.8–6.2), Pomona (4.5%; 95%CI 3.3–5.6), Canicola (3.4%; 95%CI 2.4–4.4) and Saxkoebing (0.8%; 95%CI 0.3–1.3). An association was found between positivity (MAT ≥1:100) and males (P = 0.003) and dogs that were 6 years old or older were at higher risk of exposure (P = 0.001; OR 4.61; 95%CI 1.86–11.43). This study has shown that dogs in Spain are commonly exposed to Leptospira infection and points out the necessity to control the prevalence of this severe widespread zoonosis in dogs and humans.